2020
DOI: 10.1016/j.msec.2019.110312
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation-induced osteogenesis of human adipose derived stem cells using a conductive graphene-cellulose scaffold

Abstract: Electrical stimulation-induced osteogenesis of human adipose derived Electrical stimulation-induced osteogenesis of human adipose derived stem cells Electrical stimulation-induced osteogenesis of human adipose derived stem cells using a conductive graphene-cellulose scaffold using a conductive graphene-cellulose scaffold

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 46 publications
1
42
0
Order By: Relevance
“…Reproduced with permission. [98] Copyright 2019, Elsevier. B) Charge injection cell culture set up where the conductive biomaterial is the working electrode, and an anode is submerged into the culture media.…”
Section: Conductive Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission. [98] Copyright 2019, Elsevier. B) Charge injection cell culture set up where the conductive biomaterial is the working electrode, and an anode is submerged into the culture media.…”
Section: Conductive Biomaterialsmentioning
confidence: 99%
“…Electrical stimulation of multipotent stem cells, specifically MSC and adipose stem cells (ASC), primarily are reported to enhance osteogenic differentiation, [98,120,123,125] as well as smooth muscle cells as investigated by Björninen et al [122] Zhang et al Figure 9. A) ALP activity on PPy-II electrodes with different Q inj and B) ALP activity on PPy-I and PPy-III electrodes with Q inj of 0.08 µC.…”
Section: Cellular Response To Electrical Stimulationmentioning
confidence: 99%
“…Compared with traditional metal electrodes, graphene-containing composites had lower impedance and higher charge injection capacity. For example, Li et al 92 prepared GDs-cellulose (G-C) scaffold and assembled an electrode device on this basis, which provided a platform for support and osteogenic differentiation of adipose-derived stem cell (ADSC). The results showed that the charge storage capacity of G-C electrode (0.966 mC/cm 2 ) was higher than that of gold electrode (0.462 mC/cm 2 ).…”
Section: Excellent Electrical Propertiesmentioning
confidence: 99%
“…Graphene is being intensely researched globally for applications in fields from electronics to medicine (Geim and Novoselov, 2007;Thompson et al, 2015;Ke and Wang, 2016;Kandyba et al, 2018;Li et al, 2019b). In medicine, the realization of 3D cell-supporting structures containing graphene has significant potential for tissue engineering and replacement.…”
Section: Introductionmentioning
confidence: 99%